Design of Gain Optimized Broadband Low Noise Amplifiers at 120 GHz using SiGe Technology - Chakraborty, Abhiram; Kissinger, Dietmar; Lämmle, Benjamin; Hartnagel, Hans; Weigel, Robert (German Microwave Conference, 2010)
This paper presents the design of single-ended, double stage cascode low noise amplifiers at 120 GHz. A design methodology employing three techniques for gain enhancement of the LNA is presented. The effect of traditional emitter - degeneration technique and its feasibility for simultaneous noise and power matching is evaluated at 120 GHz. The LNAs are designed in a 250 GHz fT and 300 GHz fmax 0.13 μm SiGe:C BiCMOS process. By employing the three design techniques the gain of the LNA is improved by almost 3.5 dB. The two stage gain optimized LNA achieves a gain of 24 dB and a noise figure of 7.2 dB. The circuit works with a supply voltage of 3.3 V and consumes less than 40 mW of power.
elib2cris::1512001600,chakraborty2010
Keywords: BiCMOS integrated circuits; Broadband amplifiers; Low-noise amplifiers; Noise figure; wideband amplifiers; cascode low noise amplifier; emitter-degeneration technique; 120 GHz; 250 GHz; 300 GHz; noise matching; SiGe Heterojunction Bipolar Transistor